Effects of seasonal temperature regimes on embryo growth and endogenous hormones of Taxus chinensis var. mairei seeds - Zhou, Man; Xu, Yan; Wang, Fang; Yang, Xuejun; Lu, Shunbao; Zhang, Yanjie (Frontiers in Plant Science, 2023)
Seed dormancy is a mechanism that prevents seeds from germinating in unfavorable seasons when the chance for seed survival is low by regulating dormancy status according to seasonal conditions. Determining seasonal dynamics of seed dormancy is important for revealing the adaptation of plant regeneration to the environment. We studied seed dormancy status of Taxus chinensis var. mairei, an endangered species in China, under stimulated seasonal temperature regimes. The embryo length, E:S (embryo : seed) ratio and percentage of seeds with a split seed coat increased for seeds stratified at spring and autumn temperature regimes. The ABA content decreased during stratification at simulated seasonal temperatures, but no obvious pattern in GA and IAA contents was observed. The GA/ABA and IAA/ABA ratios increased during stratification. These results suggest that T. chinensis var. mairei seeds have morphophysiological dormancy and that the seasonal dynamics of seed dormancy-break are controlled by endogenous hormones and their balances as confirmed in the field experiment. Our study provides useful information for understanding the natural population regeneration and the propagation of this threatened species.